Peluang Pengelolaan Sampah Sebagai Strategi Mitigasi Dalam Mewujudkan Ketahanan Iklim Kota Semarang - Wijayanti, Wawargita Permata (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
This study examined the opportunities in urban waste management as one of the mitigation strategies in reducing CH4 gas emission to strengthen Semarang City’s climate resilience. It was perceived as important as Semarang is one of Indonesia’s coastal cities vulnerable to the impacts of climate change. It was recognized that the vast amount of waste being dumped at the City Dump was one of the factors contributing to the high emission of CH4 gas in Semarang City. This study employed qualitative approach in identifying and describing the three factors of climate resilience namely: urban system, social agent, and urban institution, accompanied by quantitative scoring approach suggested by IPCC in finding the opportunities of several waste management strategies in building climate resilience. Analysis suggested the followings: (1) waste management at the TPST by third parties at Jatibarang City Dump may lower the emission of CH4 even exceeding the targets set by RAN-PI, (2) urban system being established was categorized as ‘sufficient’, and (3) social agent and urban institutions were categorized as ‘good’ to build climate resilience. The strategy of waste management by third parties has more opportunity to contribute in building climate resilience compared to waste management at TPST.